Précis—User-Oriented Computer Modeling Environments - Nugent, Christopher E.; Vollmann, Thomas E.; Howell, A. Harold; Schuldenfrei, Robert L.; Westfall, James R. (Management Science, 1971)
Evolution in models for problem solving is inevitable and desirable; as goals are achieved (or problems solved) new, more fundamental or telling, problems are identified leading to model revisions and better problem solutions. The speed of the evolution is dependent on two major factors: the inherent flexibility of the model and relationship of the model user to the model designer. This paper focuses on these two factors in the modeling environment. It is critical to note that the direction or course of the evolution can only be determined by users since they have the relevant goals, objectives, or criteria; expert model builders are much more capable of problem solution than of problem formulation or identification.